Systems of land assessment in Scotland before 1400 - Easson, Alexis Rachel (University of Edinburgh, 1986)
The earliest recorded system of assessment of land (or other property) in Scotland is the house system of seventh-century Dalriada. By the time documentary sources become more readily available from c. 1100 the house unit appears to have almost disappeared and between c. 1100 and c. 1400 documentary record reveals the existence of multifarious units of land assessment in Scotland. The principal units recorded during this period were the davach, the pennyland, the ounceland, the arachor and the ploughgate. The situation, however, is not as complex as it first appears. The basic framework for land assessment over most of Scotland, except the south-east, can actually be traced to the house system as recorded in seventh-century Dalriada. As regards their derivation the various land units can be grouped into two broad classes, those whose terminology implies an agrarian meaning and those which appear to have had a fiscal meaning. Regardless of their derivation and their diverse origins, which tend to reflect the influences of different cultures at different times, by c. 1100 or soon thereafter all the units were fulfilling a similar role in society. In an agricultural sense they created a structured framework within which settlement and arable developed. Fiscally they provided a base for the organisation of such fundamental prerequisites of early societies as military service and taxation. Both in their capacity as agricultural and as fiscal units the various land assessments found in Scotland before 1400 formed an integral part of the agricultural, economic and military organisation of that society.
Keywords: History